Contribuciones teóricas de las investigaciones sobre la conciencia entre el año 2000 y el año 2012 : una revisión (2014)
ABSTRACT: Consciousness is a central theme of research and psychological theorizing since the birth of the discipline. This article contains the theoretical discussion of a systematic review that analyzed 64 studies whose central topic was consciousness. Central topics found are the debate on the most appropriate methodologies to investigate its relationship with other psychological processes both at the level of environmental awareness and the level of self-awareness, and the accumulation of data suggesting clearly its main anatomical correlates.